2014
DOI: 10.1002/alr.21407
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of endoscopic maxillary mega‐antrostomy for refractory chronic maxillary sinusitis

Abstract: The original 2008 cohort of 28 patients, now with a mean follow-up period of 6.9 years, demonstrated sustained improvement of symptoms. The outcomes were statistically comparable to the 2008 study, with 72.4% reporting complete or significant improvement, 27.6% reporting partial improvement, and 0% reporting worsening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 15 publications
(22 reference statements)
0
52
0
Order By: Relevance
“…1160 The contrasts between conventional ESS and more conservative approaches, such as MIST, have been studied in patients with chronic maxillary sinusitis, and these findings have been interpreted to generally translate to the other paranasal sinuses as well. [1160][1161][1162][1163] MIST and traditional maxillary antrostomy each have their own set of potential advantages and disadvantages. Because MIST involves less manipulation of mucosa and bone, the likelihood for postoperative scar formation in the region of the maxillary ostium may be reduced.…”
Section: Surgical Principles/techinques: Extent Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…1160 The contrasts between conventional ESS and more conservative approaches, such as MIST, have been studied in patients with chronic maxillary sinusitis, and these findings have been interpreted to generally translate to the other paranasal sinuses as well. [1160][1161][1162][1163] MIST and traditional maxillary antrostomy each have their own set of potential advantages and disadvantages. Because MIST involves less manipulation of mucosa and bone, the likelihood for postoperative scar formation in the region of the maxillary ostium may be reduced.…”
Section: Surgical Principles/techinques: Extent Of Surgerymentioning
confidence: 99%
“…1161 On the other hand, clinical studies have shown that a mega-antrostomy for recalcitrant chronic maxillary sinusitis is effective in reducing sinonasal symptomatology, objective endoscopic and radiographic evidence of CRS, and corticosteroid and antibiotic use. 1162,1163 Enlargement of the maxillary ostium may also be associated with decreased NO levels in the maxillary sinus, 1164 but the clinical impact of this decrease remains unknown.…”
Section: Surgical Principles/techinques: Extent Of Surgerymentioning
confidence: 99%
“…12 MEMM has been shown to be a safe and effective surgical approach for refractory chronic maxillary sinusitis with multiple case series reporting disease resolution in up to 80% of patients with previously recalcitrant disease. 1215 Long-term follow-up of this patient cohort has confirmed lasting clinical benefit from surgery, with sustained symptomatic improvement for up to 7 years postoperatively. 15 Although the exact mechanism of improvement after MEMM has yet to be elucidated, proposed theories include improved distribution of topical therapy, improved mechanical debridement of mucus and biofilms, and facilitation of gravity-dependent sinus drainage.…”
Section: Discussionmentioning
confidence: 64%
“…1215 Long-term follow-up of this patient cohort has confirmed lasting clinical benefit from surgery, with sustained symptomatic improvement for up to 7 years postoperatively. 15 Although the exact mechanism of improvement after MEMM has yet to be elucidated, proposed theories include improved distribution of topical therapy, improved mechanical debridement of mucus and biofilms, and facilitation of gravity-dependent sinus drainage. 12 …”
Section: Discussionmentioning
confidence: 64%
“…"mega-antrostomies" in recalcitrant maxillary sinusitis. 16,17 However, it should be noted that their series contained many patients with cystic fibrosis and previous Caldwell-Luc procedures that may have already led to stagnation of mucociliary clearance and mean that the mega-antrostomy is a justifiable last resort when methods that are more conservative have failed. The mega-antrostomy is, in effect, a partial medial maxillectomy, as it involves removal of some of the inferior turbinate so that the ostium is lowered to the nasal floor and has been described as such elsewhere.…”
Section: Ijhnsmentioning
confidence: 99%